Membedah “Normalisme” Dan Stigmatisasi Gay Dalam Pemberitaan Media Di Indonesia - Nikodemus Niko (Postgraduate of Jayabaya University, 2016)
Social stigma increasingly embedded on gay in Indonesia that in fact its construction through the mass media both online and offline. Enforceability moral stigma that could be used in the society then caused the deal to deny the existence of gays in the social environment and social community. The power of media that sustain public opinion to the attitudes of the public in assessing the pseudo created normalisme. This article would like to explain that the “normal” and “abnormal” that is superficial, the irresponsible human constructions then perpetuated by human followers are also blind and also irresponsible.